Largo do Rossio to a garden: the genesis of the Gomes Freire’s square in Mariana-MG - Alves, Schirley Fátima Nogueira da Silva Cavalcante; Paiva, Patrícia Duarte de Oliveira; Garcia, Cecília Souza Gontijo (Ornamental Horticulture, 2016)
Considered as the first village from Minas Gerais state, Mariana has important cultural and historical collections from the Brazilian colonial period. Currently the city has three squares in the historic center, and they are recognized for the historical heritage. Gomes Freire’s Square, set in the historic center of Mariana, has two interesting characteristics: its location behind the Main Church and the intensity use by many social groups in this city, furthermore the large presence of tourists. In the prospect of meeting its historical evolution, and identify the landscape representation in the collective unconscious of Mariana’s inhabitants, it was analyzed the evolution of the village and formation of the Gomes Freire’s Square. To achieve this goal it was necessary to deepen the knowledge of the social appropriation of this space over time, enabling the identification of the same, as well as its evolution as a public place. The study focused its interest in the village evolution, in the uses and social representation of the covered space. For this, the methodology applied was an interface between the inventive analysis, subjective method analysis, and recommendations for preservation of historic gardens. Gomes Freire’s Square, in its formation process presented as remarkable feature in its historical dimension, the fact that emerged and remained as a space of popular demonstrations.